Never nice? Love, loneliness and poetry in the correspondence of Sylvia Plath - Sullivan, H (Times Newspapers Ltd., 2019)
Review of Volume 1 and Volume 2 of The Letters of Sylvia Plath, edited by Peter K. Steinberg and Karen V. Kukil. Discusses the correspondence with Ruth Beuscher, her psychiatrist, and her relationship with Ted Hughes.